Effects of Audio Feedback in an Online Assessment in Students' Academic Motivation - Jerry Jr. Escultura; Amniel Mejico (Camarines Sur Polytechnic Colleges, 2023)
Many research has revealed that feedback has a big impact on students' learning and is the most effective single moderator of achievement enhancement. Hence, this study aimed to determine the effects of giving audio feedback in an online assessment on students' academic motivation. The participants in this study are 49 senior high school students who have the same online assessments. A mixed-methods research design was utilized in this study. The results showed that there was no significant difference in academic motivation between the students before and after applying the audio feedback in their online assessments and were indicative of high academic motivation throughout the experiment. However, the students' experiences revealed the following factors: (1) Student Emotional Engagement; (2) Comprehensive Understanding through Audio Feedback; (3) Students' Receptiveness in Audio Feedback; (4) Utilization of Feedback in Improving Students' Work; and (5) Improve Students' Motivation. Overall, even though the audio feedback doesn't greatly affect the students' academic motivation, it still creates a better experience in providing feedback to the students as it is used for their improvement on their online assessment. This study has broad implications in the online learning environment and creates new paths that teachers may take in giving feedback in their online assessment to make it personalized and comprehensible for the improvement of students' work.